Example 1
Solve the following equation for z3:
z3 + 3(z + 2) – 4 = 2z + 4(z + 1) – 3z
Example 2
Solve for x5:
x2(x3 + 2) – 2y = y + 2x2
Example 3
Solve for 2y:
4y + 16 = 8x – 3
We have changed our privacy policy. In addition, we use cookies on our website for various purposes. By continuing on our website, you consent to our use of cookies. You can learn about our practices by reading our privacy policy.
Solve the following equation for z3:
z3 + 3(z + 2) – 4 = 2z + 4(z + 1) – 3z
Solve for x5:
x2(x3 + 2) – 2y = y + 2x2
Solve for 2y:
4y + 16 = 8x – 3